PERLINDUNGAN HUKUM USAHA MIKRO KECIL DAN MENENGAH INDUSTRI OBAT TRADISIONAL DI JAWA TIMUR TERHADAP DAMPAK DARI MASYARAKAT EKONOMI ASEAN (MEA) - Subarjo Subarjo (Legal Spirit, 2019)
In this study shows that the Asean Economic Community (AEC) does not protect the economic interests of the Micro Small and Medium Enterprises in the Traditional Medicine Industry in East Java because 1) national law inhibits capital, guidance or has not been able to protect price competition from global markets, 2) business competition policies Asean cannot guarantee legal certainty and protect against unfair competition among member States because it is a reference and not binding on each of its members, 3) There is a dishonorisation between the 1945 Constitution with international provisions on the Asean Economic Community (AEC), and 4) The results of harmonization of the Agreement Traditional medicines are not able to be carried out by the traditional medicine industry because the rules are equated with chemical drugs thatrequire expensive facilities and infrastructure and good buildings. Furthermore, legal construction so that the UMKM of the Traditional Medicine Industry is protected from the impact of the AEC is to extend the preparation period, the government provides capital support, and creates regulations that favor traditional drug business actors by providing clear legal certainty regarding certificates for making good traditional medicines ( CPOTB)